Client Satisfaction of Public and Private Rehabilitation Day Centers in Kordestan Province - Nikta Hatami-Zadeh; Parvin Ja'fari; Roshanak Vameghi; Anoushirvan Kazem-Nezhad (University of Social Welfare and Rehabilitation Sciences, 2008)
Objective: In this study clients' satisfaction in public and private rehabilitation centers in Kordestan province was assessed and compared. Materials & Methods: In this comparative and cross-sectional study, 415 people who were admitted for the first time to out patient public and private rehabilitation centers in Kurdistan, during the six month period of autumn and winter 1383, were selected by simple randomized and stratified sampling. Using a structured questionnaire, information was gathered through telephone interviews, and each client's satisfaction measured and scored by 1-20. The questionnaire's face validity was approved by experts. Using the test- retest method, the reliability was r = 0.83 and it's ICC was 0.76 (Kronobakh alpha). Independent t- test and Chi-Square test were used to analyze of data. Results: The total satisfaction score of public sector clients (12.48±1.6) was more than that of private sector clients (12.15±1. 4) and their difference was significant (P=0.04). The private sector clients were more satisfied than public sector clients with physical conditions (P<0.001), time accessibility (P=0.018) and communication skills of the personnel (P=0.018), but the mean difference was not more than 1 point in either area. In public centers the physical accessibility (P=0.01), financial accessibility (P<0.001) and quality of services (P<0.001) caused significant higher satisfaction than private centers. Conclusion: Although the difference between clients' satisfaction in public centers and private ones was statistically significant, but the differences were not so prominent, except in the case of financial accessibility. Attaining a higher quality rehabilitation services and enhancing client satisfaction, is necessary for both public and private centers. For the private sector we extension of insurance coverage is recommended.